1992
DOI: 10.12693/aphyspola.81.687
|View full text |Cite
|
Sign up to set email alerts
|

Measurement System for Fractional Glow Technique

Abstract: Some details of computerized arrangement for recording fractional thermoluminescence at high temperatures are presented. The investigation of energy distribution of traps for quartz crystals exemplifies the measurement procedure and data handling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Standard deviations from the linear heating profiles of less than 0.05 • C were obtained for both heating rates. These characteristics are comparable to those research instruments reported earlier [5][6][7].…”
Section: Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Standard deviations from the linear heating profiles of less than 0.05 • C were obtained for both heating rates. These characteristics are comparable to those research instruments reported earlier [5][6][7].…”
Section: Performancesupporting
confidence: 89%
“…There are many reports of setups for TL and FGT measurements, but most of them are based on specific expensive data acquisition PC-boards, and do not always ensure the temperature control precision necessary for FGT [5][6][7]. The peculiarity of the described system is that it is microcontroller-based and needs no additional PC-boards.…”
Section: Introductionmentioning
confidence: 99%
“…The normal glow curve was registered with constant heating rate w = 0.2o C/s. For a detailed description of our experimental setup the reader is referred to [19].…”
Section: Methodsmentioning
confidence: 99%